2015
DOI: 10.1016/j.jscs.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of TiO2 quantum dots for photocatalytic application

Abstract: In the present study, TiO 2 quantum dots (QDs) were effectively synthesized by the solgel method and it was characterized by several techniques. The structure of the TiO 2 QDs, before and after calcination, was analyzed by the powder X-ray diffraction technique. The XRD results indicate that after calcination, TiO 2 QDs have pure anatase phase with tetragonal structure without any other phases and impurities. The morphology and size of the TiO 2 QDs were determined from FE-SEM and TEM analysis. The optical ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…TiO 2 is also a wide energy bandgap material, typically displaying optical bandgaps of 3.0 and 3.2 eV for rutile and anatase, respectively, and varying from 3.13 to 3.40 eV for brookite [18,19]. Both metal oxides are environmentally friendly, earth abundant, chemically stable, low-cost, nontoxic, and compatible with wetchemical synthesis routes [20][21][22][23]. For both materials above described, there are several reports describing the use of hydrothermal/solvothermal synthesis to produce them [24][25][26][27], while more recently assisted process methods by microwave irradiation have been deeply exploited [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 is also a wide energy bandgap material, typically displaying optical bandgaps of 3.0 and 3.2 eV for rutile and anatase, respectively, and varying from 3.13 to 3.40 eV for brookite [18,19]. Both metal oxides are environmentally friendly, earth abundant, chemically stable, low-cost, nontoxic, and compatible with wetchemical synthesis routes [20][21][22][23]. For both materials above described, there are several reports describing the use of hydrothermal/solvothermal synthesis to produce them [24][25][26][27], while more recently assisted process methods by microwave irradiation have been deeply exploited [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a variety of synthetic methods to prepare TiO 2 xerogel and aerogel have been utilized while varying the pH of solution (acid-catalyzed or basic-catalyzed) and the drying processes such as supercritical (aerogel) or conventional drying (xerogel). The application of TiO 2 in photodegradation of organic pollutants in water has also been discussed in literature [35][36][37][38][39][40][41][42][43][44][45][46][47][48] and it is reported that surface, structural properties and photocatalytic efficiency depend strongly on the method used for the preparation of materials. However, there is no direct correlation between surface proprieties and photoactivity of TiO 2 [49].…”
Section: Introductionmentioning
confidence: 99%
“…This shows that the presence of BEN-PVAG as the adsorbent sub-layer for P-25TiO 2 in the fabrication of P-25TiO 2 / BEN-PVAG/GP lowered the crystallinity of the photocatalyst, potentially due to the presence of the polymeric binders. The XRD pattern of P-25TiO 2 /BEN-PVAG/GP shows diffraction peaks at 2h = 25.3°, 37.8°, 48.0°, 53.9°, 55.1°, 62.6°, 66.3°, and 68.9°which correspond to the (101), (103), (200), (105), (211), (213), (116), and (220) crystalline plane of the anatase phase, respectively (Gnanasekaran et al 2015). Other peaks at 2h = 27.5°and 41.4°are attributed to the (110) and (111) diffraction planes of rutile.…”
Section: Resultsmentioning
confidence: 99%
“…Removal techniques of dye molecules from waste water include physical (Eren 2009;Silva et al 2012), chemical (Nawi and Sabar 2012;Saravanan et al 2013) and biological processes (López et al 2006;Selvakumar et al 2010). Among these methods, adsorption using porous materials and heterogeneous photocatalysis (Gnanasekaran et al 2015) had been demonstrated as promising techniques.…”
Section: Introductionmentioning
confidence: 99%